Evaluación de una estrategia de formación en educación STEAM para docentes de ciencias naturales de cuatro colegios públicos de Bogotá - Edison Camacho Tamayo (Universidad Antonio Nariño, 2024)
STEAM education has aroused great interest in the scientific community due to the positive effect that it might have on educational processes. However, teacher training in this approach for improving classroom practices in the teaching and learning of scientific knowledge is an issue that still requires attention. For this reason, this research aims to evaluate a training strategy in the STEAM approach, through a mixed methodological design, with twenty-one natural science teachers in the city of Bogota. The results show that the strategy generates reflection on the teachers' work, exposes a training methodology that suits their needs and contributes to the empirical research on the STEAM approach. As a conclusion, it is identified that the STEAM training strategy has a level of reaction, learning and positive behavior in natural science teachers.